Integrated Mechanized System of Agro-Aquaculture System: Sustainable Farming Model for Poultry, Catfish, and Small Scale Farm. - Ekpechi, Daniel; Nwufo, Olisaemeka Chukwudozie; Asonye, Gladys Uche; Emeziem, Victor Chukwuemeka; Nwankwo, Anthony Chukwudi; Kalu, Okafor; Oguoma, Onyewuchi Nduwuishi (Accurate: Journal of Mechanical Engineering and Science, 2025)
One of the major factors that makes up a developed country is the ability to feed themselves, which agricultural system of a country needs to be enhanced to achieve such standard. This research presents the design and development of a mechanized integrated farming system, uniting poultry, fishpond, and small scale corn plantation. The methodology of this research includes conceptual design and principle of operation of the intended design, application mathematical models and machine design principles to determine the required dimensions of the machine structural parts, conveyor components, and solar energy, then material selection and assembly of the entire mechanism. Afterward, the developed machine was used to rear chicken, fish and small scale corn plantation as well as traditional means and cost comparison of the two methods were conducted. From the result obtained, a chicken prototype farm with 125 cm x 35 cm x 40 cm dimension comfortable enough to house 5 chicken and fish, and a solar energy of 750 W which conveys chicken droppings on speed of 0.0679 m/s was established. Furthermore, the comparative cost analysis shows that integrated farming reduces poultry and catfish feed costs by 20% and 40%, respectively, while surpassing traditional farming in savings and profitability by over 200%. The mechanized integrated farming system presented a sustainable and resource-efficient model, maximizing waste utilization, reducing environmental impact, and promoting ecological balance. This research contributes to evolving agricultural practices, offering insights for diverse farming systems.